Users' reactions captured by means of an EEG headset on viewing the presentation of sustainable designs using verbal narrative. (12th February 2018) - Royo, Marta; Chulvi, Vicente; Mulet, Elena; Galán, Julia
Abstract : Purpose: The aim of this paper is to determine whether consumers accept new arguments for choosing a product that adapts to future needs. It is also seeking to investigate whether the design of products and their ensuing advertising and promotion through a sustainable approach by means of verbal narrative ads can generate a more positive emotional response in the future users of the product than with the application of visual narrative ads. Design/methodology/approach: To this end, an experiment was conducted consisting of consumers, with and without experience with the product, watching a promotional video based on verbal narrative, created using the new usage scenarios approach, in which the advantages of a sustainable product are shown. The neuronal response of the possible users was then measured by means of the electroencephalogram (EEG) headset. To be able to establish a comparison, the same response was also measured in the same consumers when they viewed a commercial video based on visual narrative about a product with similar characteristics. Findings: The results show, among other conclusions, that viewing the verbal narrative ad first triggers higher emotional values of excitement, both in the short and the long term, as well as frustration. It is also observed that having no experience with the product causes higher meditation values. Practical implications: This research pretends to discern the emotional effect of watching a green advertisement in the consumers. This can be useful to enterprises both to design their products to orientate them to consumer concerns, and to design the advertisements to emotionally link consumers with the product. Originality/value: This can be useful to enterprises both to design their products in such a way as to orientate them towards consumer concerns, and to design advertisements in such a way as to link consumers emotionally with the product.